REVIVAL OF SPIRITUAL VALUES IN THE SOCIAL TRANSFORMATION AND NATIONAL IDENTITY (American Journal of Pedagogical and Educational Research, 2022)
The cultural values of the people and their spiritual heritage have served as a powerful source of spirituality for the peoples of the East for thousands of years. Despite the harsh ideological pressure for a long period, the people of Uzbekistan managed to preserve their historical and cultural values and original traditions, which were carefully passed down from generation to generation.